Sulfide solid electrolyte and all-solid-state battery

By introducing Al and N elements into the sulfide solid electrolyte to form a sulfide electrolyte with a crystal structure, the problem of insufficient degradation and reduction of the existing sulfide solid electrolyte is solved, and its degradation and reduction properties are significantly improved, and the safety of the battery and the initial Colm efficiency are enhanced.

JP2025069365APending Publication Date: 2025-04-30GS YUASA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025017196
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-06-03
Filing Date
2025-02-05
Publication Date
2025-04-30

AI Technical Summary

Technical Problem

The existing sulfide solid electrolytes have shortcomings in reducing the formation of hydrosulfide in the environment, and their degradation and reduction properties are low, which affects the safety and performance of the battery.

Method used

By introducing Al and N elements into the sulfide solid electrolyte, a sulfide electrolyte with a crystal structure is formed, thereby improving its degradation and reducing properties.

Benefits of technology

The degradation and reduction properties of sulfide solid electrolyte are significantly improved, their ability to inhibit hydrosulfide generation is enhanced, and the safety of the battery and the first Colm efficiency are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069365000001_ABST
    Figure 2025069365000001_ABST
Patent Text Reader

Abstract

To provide a sulfide-based solid electrolyte having enhanced reduction resistance and an all-solid-state battery comprising the sulfide-based solid electrolyte.SOLUTION: A sulfide-based solid electrolyte contains Al and N and has a crystalline structure. In an all-solid-state battery 10, a negative electrode layer 1 and a positive electrode layer 2 are disposed with a solid electrolyte layer 3 placed between them. The negative electrode layer 1 includes a negative current collector layer 4 and a negative composite layer 5, with the negative current collector layer 4 serving as the outermost layer of the negative electrode layer 1. The positive electrode layer 2 includes a positive current collector layer 7 and a positive composite layer 6, with the positive current collector layer 7 serving as the outermost layer of the positive electrode layer 2. Laminated in this order on the positive current collector layer 7 are the positive composite layer 6, the solid electrolyte layer 3, the negative composite layer 5, and the negative current collector layer 4.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sulfide solid electrolyte and an all-solid-state battery. [Background technology]

[0002] Due to their high energy density, non-aqueous electrolyte secondary batteries, such as lithium ion non-aqueous electrolyte secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc. The non-aqueous electrolyte secondary batteries generally include an electrode assembly having a pair of electrically isolated electrodes, and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes.

[0003] In recent years, with the aim of improving the safety of non-aqueous electrolyte secondary batteries, all-solid-state batteries have been proposed that use a sulfide solid electrolyte or the like as the non-aqueous electrolyte instead of a liquid electrolyte such as an organic solvent (see Patent Document 1).

[0004] As an example of a sulfide solid electrolyte, a sulfide solid electrolyte that contains Li, P, S, and N and has a composition expressed by the general formula XLi2S-25P2S5-YLi3N (10≦Y≦15, 67.5≦X+Y≦85), and is a crystalline material, has been disclosed (see Patent Document 2). As sulfide solid electrolytes, 70Li2S 30P2S5 glass ceramics and 60Li2S 25P2S5 10Li3N glass ceramics are used. -3 It has been reported that it exhibits high ionic conductivity of more than S / cm. (Non-Patent Document 1)

[0005] First-principles calculations have revealed that such sulfide solid electrolytes are inherently poor in oxidation resistance and reduction resistance (Non-Patent Document 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2000-340257 A [Patent Document 2] JP 2018-041671 A [Non-Patent Document 1] Solid State Ionics,177,2721(2006), Solid State Ionics,304,85(2016) [Non-Patent Document 2] ACS Appl.Mater.Interfaces, 7, 23685(2015) Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made based on the above circumstances, and has an object to provide a sulfide solid electrolyte having improved reduction resistance and an all-solid-state battery including the sulfide solid electrolyte. [Means for solving the problem]

[0008] One aspect of the present invention made to solve the above problems is a sulfide solid electrolyte having a crystalline structure, comprising N and at least one element M selected from the group consisting of Al, Si, B, Mg, Zr, Ti, Hf, Ca, Sr, Sc, Ce, Ta, Nb, W, Mo, and V.

[0009] Another embodiment of the present invention is a sulfide solid electrolyte containing Al and N and having a crystal structure. Effect of the Invention

[0010] According to the sulfide solid electrolyte according to one or another aspect of the present invention, it is possible to provide a sulfide solid electrolyte having improved reduction resistance. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an all-solid-state battery according to one embodiment of the present invention. [Diagram 2] 1 shows X-ray diffraction (XRD) spectra of sulfide solid electrolytes of Examples and Comparative Examples. [Diagram 3] 1 shows Raman spectra of sulfide solid electrolytes of Examples and Comparative Examples. [Figure 4] 1 is a graph showing the ionic conductivity at 25° C. of sulfide solid electrolytes of Examples and Comparative Examples. [Diagram 5] 1 is a graph showing the initial charge / discharge performance of all-solid-state batteries of Examples and Comparative Examples. [Figure 6] 1 is a graph showing the amount of hydrogen sulfide generated from sulfide solid electrolytes of Examples and Comparative Examples. [Figure 7] 1 is a graph showing the amount of hydrogen sulfide generated from the sulfide solid electrolytes of Examples and Reference Examples. [Figure 8] 1 shows X-ray diffraction (XRD) spectra of sulfide solid electrolytes of Examples, Comparative Examples, and Reference Examples. [Figure 9] 4 is a dQ / dV curve of the all-solid-state batteries of Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] A sulfide solid electrolyte according to one embodiment of the present invention is a sulfide solid electrolyte having a crystalline structure, which contains N and at least one element M selected from the group consisting of Al, Si, B, Mg, Zr, Ti, Hf, Ca, Sr, Sc, Ce, Ta, Nb, W, Mo, and V.

[0013] The present inventors have noticed that nitrides containing any one of Al, Si, B, Mg, Zr, Ti, Hf, Ca, Sr, Sc, Ce, Ta, Nb, W, Mo, and V (hereinafter also referred to as element M), which are difficult to use as solid electrolytes due to their low ionic conductivity, exhibit high reduction resistance. Therefore, they have thought that the reduction resistance of a sulfide solid electrolyte can be improved by including nitrogen element (N) and element M in the sulfide solid electrolyte, and have arrived at the present invention.

[0014] The sulfide solid electrolyte contains at least one element M selected from the group consisting of Al, Si, B, Mg, Zr, Ti, Hf, Ca, Sr, Sc, Ce, Ta, Nb, W, Mo, and V, and N, and has a crystal structure, so that the sulfide solid electrolyte has improved reduction resistance. In the sulfide solid electrolyte, the element M may be Al. Although the reason for this is not clear, the following reason is presumed. When the sulfide solid electrolyte containing the elements M and N is exposed to a reducing atmosphere, it is presumed that a highly reduction-resistant coating containing a nitride of the element M or a lithium nitride of the element M is formed on the surface or interface of the sulfide solid electrolyte. For this reason, it is presumed that the reduction resistance of the sulfide solid electrolyte is improved.

[0015] An all-solid-state battery including the sulfide solid electrolyte can be an all-solid-state battery with improved initial coulombic efficiency. The reason for this is unclear, but the following reason is presumed. It is known that general sulfide solid electrolytes are easily reductively decomposed, and that all-solid-state batteries including such sulfide solid electrolytes exhibit a large amount of electricity due to reductive decomposition, but the sulfide solid electrolyte has high resistance to reduction. This makes it possible to improve the initial coulombic efficiency of an all-solid-state battery including the sulfide solid electrolyte. Furthermore, when the sulfide solid electrolyte contains N, S is replaced by N, which has a small ionic radius, reducing the crystal lattice volume. This increases the space for lithium ions to move, improving ionic conductivity. As a result, the initial coulombic efficiency of the all-solid-state battery can be improved while maintaining good ionic conductivity.

[0016] The element M in the sulfide solid electrolyte may be any element that has high resistance to reduction of the nitride. Specifically, it may be at least one element selected from the group consisting of Al, Si, B, Mg, Zr, Ti, Hf, Ca, Sr, Sc, Ce, Ta, Nb, W, Mo, and V. These elements are elements that have been shown by first-principles calculations to have high resistance to reduction of lithium nitrides containing the element M (see non-patent document Adv. Sci., 4, 1600517 (2017)). Among these, Al, B, and Si are preferred because they have low cost and can reduce manufacturing costs.

[0017] The above crystal structure is Li7P3S 11 It is preferable that the crystalline structure has a crystal phase of Li4P2S6 or β-Li3PS4, or a first crystal structure having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, and 29.8°±0.5° in X-ray diffraction measurement using CuKα radiation. This can increase the ionic conductivity at 25°C.

[0018] It is preferable that the first crystal structure includes a specific crystal structure A having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, 29.8°±0.5°, and 30.9°±0.5° in the X-ray diffraction measurement, or a specific crystal structure B having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, and 29.8°±0.5° and no diffraction peak at 30.9°±0.5° in the X-ray diffraction measurement. With the above configuration, the ionic conductivity at 25°C can be further increased.

[0019] When the sulfide solid electrolyte contains at least one element M selected from the group consisting of Li, P, S, N, and Al, Si, B, Mg, Zr, Ti, Hf, Ca, Sr, Sc, Ce, Ta, Nb, W, Mo, V, from the viewpoint of reduction resistance, the content ratio of Li to P is preferably 1.64 or more and 4.00 or less in terms of molar ratio, and the content ratio of N to P is preferably 0.02 or more and 1.11 or less in terms of molar ratio. When the content ratios of Li and N in the sulfide solid electrolyte are within the above ranges, the reduction resistance is further improved, and the initial Coulomb efficiency of the all-solid-state battery provided with the sulfide solid electrolyte can be further increased. In the sulfide solid electrolyte, the element M may be Al.

[0020] In the sulfide solid electrolyte, it is more preferable that the content ratio of Li to P is 2.77 or more and 3.38 or less in terms of molar ratio, and the content ratio of N to P is 0.28 or more and 0.65 or less in terms of molar ratio. When the content ratios of Li and N in the sulfide solid electrolyte are within the above ranges, the reduction resistance, the air stability, and the ionic conductivity at 25 °C can be simultaneously increased.

[0021] When the sulfide solid electrolyte is (100 - z)(yLi₂S·(1 - y)P₂S₅)·zLi α M β N (where 0 < z ≤ 40, 0.50 ≤ y ≤ 0.75, α and β are numerical values giving the stoichiometric ratio according to the type of element M), it preferably has a composition represented by this. When the sulfide solid electrolyte has a composition represented by the above general formula, the reduction resistance is further improved, and the initial Coulomb efficiency of the all-solid-state battery provided with the sulfide solid electrolyte can be further increased.

[0022] The sulfide solid electrolyte may further contain Ge. Even such a sulfide solid electrolyte can enjoy the effects of the present invention.

[0023] When the sulfide solid electrolyte contains Ge, the sulfide solid electrolyte is Li 10 GeP₂S 12Preferably, it includes a structure having a crystal phase.

[0024] Further, the sulfide solid electrolyte contains Li, P, S, N, Ge, and the above element M, and Li 10 GeP2S 12 When it has a crystal phase, the content ratio of Li to P is preferably 5.01 or more and 5.61 or less in molar ratio, and the content ratio of N to P is preferably 0.0051 or more and 0.41 or less in molar ratio. Further, it is more preferable that the content ratio of Li to P is 5.06 or more and 5.19 or less in molar ratio, and the content ratio of N to P is 0.038 or more and 0.13 or less in molar ratio.

[0025] When the sulfide solid electrolyte contains Ge, it preferably has a composition represented by the general formula (100 - z)Li 10 GeP2S 12 ·zLi α M β N (where 0 < z ≤ 50, α and β are numerical values giving a stoichiometric ratio according to the type of element M). Among them, in the above general formula, it is particularly preferable that z satisfies 0 < z ≤ 20.

[0026] The ionic conductivity of the sulfide solid electrolyte at 25°C is preferably 1.0×10 -3 S / cm or more. With the above configuration, the high-rate discharge performance of the all-solid-state battery provided with the sulfide solid electrolyte can be improved.

[0027] The ionic conductivity of the sulfide solid electrolyte at 25°C is determined by measuring the AC impedance using the following method. In an argon atmosphere with a dew point of -50°C or less, 120 mg of sample powder is placed in a powder molder with an inner diameter of 10 mm, and then uniaxially pressurized with a hydraulic press at a pressure of 50 MPa or less per sample area. After releasing the pressure, SUS316L powder is placed on the top and bottom of the sample as a current collector, and then uniaxially pressurized for 5 minutes at a pressure of 360 MPa per pellet area to obtain a pellet for ionic conductivity measurement. The pellet for ionic conductivity measurement is inserted into a Hohsen HS cell to measure the AC impedance. The measurement conditions are an applied voltage amplitude of 20 mV, a frequency range of 1 MHz to 100 mHz, and a measurement temperature of 25°C.

[0028] An all-solid-state battery according to another aspect of the present invention is an all-solid-state battery including an anode layer, a solid electrolyte layer, and a cathode layer, in which the anode layer, the solid electrolyte layer, the cathode layer, or a combination thereof contains the sulfide solid electrolyte.

[0029] In the all-solid-state battery according to another aspect of the present invention, the negative electrode layer, the solid electrolyte layer, the positive electrode layer, or a combination thereof contains the sulfide solid electrolyte, and therefore the initial coulombic efficiency is excellent. Since the sulfide solid electrolyte has excellent resistance to reduction, it is preferable that the negative electrode layer and / or the solid electrolyte layer contains the sulfide solid electrolyte. With the above configuration, the effects of the present invention are further improved.

[0030] Hereinafter, embodiments of the sulfide solid electrolyte and the all-solid-state battery according to the present invention will be described in detail.

[0031] <Sulfide solid electrolyte> The sulfide solid electrolyte contains at least one element M selected from the group consisting of Al, Si, B, Mg, Zr, Ti, Hf, Ca, Sr, Sc, Ce, Ta, Nb, W, Mo, and V, and N, and has a crystal structure. The sulfide solid electrolyte contains at least one element M selected from the group consisting of Al, Si, B, Mg, Zr, Ti, Hf, Ca, Sr, Sc, Ce, Ta, Nb, W, Mo, and V, and N, and has a crystal structure, thereby improving reduction resistance. The sulfide solid electrolyte can be used for any application requiring ion conductivity. Among them, the sulfide solid electrolyte is preferably used in a lithium all-solid-state battery. In the sulfide solid electrolyte, the element M may be Al.

[0032] The sulfide solid electrolyte has a crystalline structure. Here, "having a crystalline structure" means that a peak derived from the crystalline structure of the sulfide solid electrolyte is observed in an X-ray diffraction pattern in an X-ray diffraction measurement. The sulfide solid electrolyte may contain an amorphous portion. The sulfide solid electrolyte having a crystalline structure can be obtained, for example, by crystallizing an amorphous sulfide solid electrolyte by heat treatment or the like.

[0033] Examples of the crystal structure of the sulfide solid electrolyte include LGPS type, argyrodite type, Li7P3S 11 Among these, the crystal structures mentioned above are LGPS type, Argyrodite type, and Li7P3S, from the viewpoint of lithium ion conductivity. 11 is preferred, and among these, Li7P3S is preferred because it has high stability against Li. 11From the viewpoint of stability against the atmosphere, it is preferable to include a crystal structure having a crystal phase of Li4P2S6 or β-Li3PS4, or a first crystal structure having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, and 29.8°±0.5° in X-ray diffraction measurement using CuKα radiation, and among these, it is more preferable to be the first crystal structure having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, and 29.8°±0.5° in X-ray diffraction measurement using CuKα radiation, because of its high lithium ion conductivity.

[0034] The first crystal structure may include a specific crystal structure A having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, 29.8°±0.5°, and 30.9°±0.5° in the X-ray diffraction measurement, or a specific crystal structure B having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, and 29.8°±0.5° but no diffraction peak at 30.9°±0.5° in the X-ray diffraction measurement. With the above configuration, the ionic conductivity at 25°C can be increased.

[0035] The diffraction peak in the first crystal structure may be within the range of ±0.3°, or may be within the range of ±0.1° of the range of 2θ.

[0036] The X-ray diffraction measurement using CuKα radiation is carried out according to the following procedure. The solid electrolyte powder to be measured is filled into an airtight sample holder for X-ray diffraction measurement in an argon atmosphere with a dew point of -50°C or less. Powder X-ray diffraction measurement is carried out using an X-ray diffraction device (MiniFlex II, manufactured by Rigaku). The radiation source is CuKα radiation, the tube voltage is 30 kV, the tube current is 15 mA, and the diffracted X-rays are passed through a 30 μm thick Kβ filter and detected by a high-speed one-dimensional detector (model number: D / teX Ultra 2). The sampling width is 0.01°, the scan speed is 5° / min, the divergence slit width is 0.625°, the receiving slit width is 13 mm (OPEN), and the scattering slit width is 8 mm.

[0037] The above Li7P3S 11 The crystal structure having this crystalline phase has diffraction peaks at 2θ=17.8°±0.5°, 18.5°±0.5°, 23.7°±0.5°, 29.6°±0.5°, and 30.0°±0.5° in X-ray diffraction measurement using the above-mentioned CuKα radiation.

[0038] The LGPS-type sulfide solid electrolyte may be, for example, Li 10 GeP2S 12 Li 10 GeP2S 12 The crystal structure having this crystalline phase has diffraction peaks at 2θ=14.4°±0.5°, 20.1°±0.5°, 20.4°±0.5°, 26.9°±0.5°, 29.5°±0.5°, and 47.3°±0.5° in X-ray diffraction measurement using the above-mentioned CuKα radiation.

[0039] The argyrodite-type sulfide solid electrolyte may be, for example, Li6PS5Cl, etc. The crystal structure having the Li6PS5Cl crystal phase has diffraction peaks at 2θ=15.6°±0.5°, 25.5°±0.5°, 30.0°±0.5°, 31.4°±0.5°, 45.0°±0.5°, and 52.5°±0.5° in the X-ray diffraction measurement using the CuKα ray.

[0040] The crystal structure having the above Li4P2S6 crystalline phase has diffraction peaks at 2θ=16.9°±0.5°, 27.1°±0.5°, 32.1°±0.5°, and 32.5°±0.5° in X-ray diffraction measurement using the above CuKα radiation.

[0041] The crystal structure having the above β-Li3PS4 crystalline phase has diffraction peaks at 2θ=17.5°±0.5°, 18.1°±0.5°, 29.1°±0.5°, 29.9°±0.5°, and 31.2°±0.5° in X-ray diffraction measurement using the above CuKα radiation.

[0042] The sulfide solid electrolyte preferably contains Li, P, S, N, and element M. In this case, from the viewpoint of reduction resistance, the content ratio of Li to the P in the sulfide solid electrolyte is preferably 1.64 to 4.00 in molar ratio, more preferably 2.36 to 3.70, and even more preferably 2.60 to 3.40. The content ratio of N to the P is preferably 0.02 to 1.11, more preferably 0.19 to 1.01, even more preferably 0.22 to 0.71, and particularly preferably 0.28 to 0.65. When the content ratios of Li and N in the sulfide solid electrolyte are within the above ranges, a sulfide solid electrolyte exhibiting good reduction resistance can be obtained. In addition, the initial coulombic efficiency of an all-solid-state battery including the sulfide solid electrolyte can be increased.

[0043] Furthermore, from the viewpoint of stability in the atmosphere, it is preferable that the molar ratio of the Li to the P is 2.60 or more and 4.00 or less, and the molar ratio of the N to the P is 0.19 or more and 1.11 or less, and it is more preferable that the molar ratio of the Li to the P is 2.77 or more and 3.38 or less, and the molar ratio of the N to the P is 0.28 or more and 0.65 or less. It is also preferable that the element M contains Al. This makes it possible to obtain a so-called bridged sulfur P2S7 which is unstable in the atmosphere, particularly when the value of y in the general formula is less than 0.75. 4- Since the amount of (S3P-S-PS3) is reduced and the sulfide solid electrolyte does not substantially contain Li2S, which easily reacts with water, the atmospheric stability of the sulfide solid electrolyte is improved and the generation of hydrogen sulfide due to the reaction between moisture in the air and S in the sulfide solid electrolyte can be suppressed.

[0044] In particular, it is preferable that the molar ratio of the Li content to the P content is 2.77 or more and 3.38 or less, and the molar ratio of the N content to the P content is 0.28 or more and 0.65 or less, since this can simultaneously increase the reduction resistance, the atmospheric stability, and the ionic conductivity at 25°C.

[0045] The sulfide solid electrolyte contains Li, P, S, N, Ge, and the element M, and Li10 GeP2S 12 When it has a crystal phase of, from the viewpoint of reduction resistance, the content ratio of Li to P is preferably 5.01 or more and 5.61 or less in molar ratio, and the content ratio of N to P is preferably 0.0051 or more and 0.41 or less in molar ratio. Further, it is more preferable that the content ratio of Li to P is 5.06 or more and 5.19 or less in molar ratio, and the content ratio of N to P is 0.038 or more and 0.13 or less in molar ratio.

[0046] As the sulfide solid electrolyte, it preferably has a composition represented by the general formula (100 - z)(yLi2S·(1 - y)P2S5)·zLi α M β N (where 0 < z ≤ 40, 0.50 ≤ y ≤ 0.75,). When the sulfide solid electrolyte has a composition represented by the above general formula, the reduction resistance can be further improved. Further, the initial Coulomb efficiency of the all - solid - state battery including the sulfide solid electrolyte can be further increased.

[0047] In the above general formula, z is preferably more than 0 and 40 or less, more preferably 1 or more and 30 or less, still more preferably 1 or more and 5 or 10 or more and 30 or less, and even more preferably 1 or more and 5 or 10 or more and 25 or less. When z in the above general formula is in the range of more than 0 and 40 or less, the reduction resistance of the sulfide solid electrolyte can be further improved. When 10 ≤ z ≤ 40, so - called cross - linked sulfur P2S7 4- (S3P - S - PS3) decreases and it substantially does not contain Li2S which easily reacts with water. Therefore, the air stability of the sulfide solid electrolyte is improved, and the generation of hydrogen sulfide due to the reaction between moisture in the air and S in the sulfide solid electrolyte can be suppressed. When 1 ≤ z ≤ 30, the ionic conductivity at 25°C can be further increased. When 1 ≤ z ≤ 5 or 10 ≤ z ≤ 30, the ionic conductivity at 25°C can be further increased. When 1 ≤ z ≤ 5 or 10 ≤ z ≤ 25, the ionic conductivity at 25°C can be even further increased.

[0048] In the above general formula, y is preferably 0.50 or more and 0.75 or less, and more preferably 0.67 or more and 0.70 or less. When the content ratios of Li2S and P2S5 in the sulfide solid electrolyte are within the above ranges, the ionic conductivity of the sulfide solid electrolyte at 25 °C is improved.

[0049] In the above general formula, α and β are numerical values that give a stoichiometric ratio according to the type of element M. The values of α and β are not particularly limited, and for example, 0.80 ≤ α ≤ 3.0 and 0.10 ≤ β ≤ 1.2 may be used. In particular, when the element M contains Al, α = 1.5 and β = 0.5 may be used.

[0050] When the sulfide solid electrolyte contains Ge, it preferably has a composition represented by the general formula (100 - z)Li 10 GeP2S 12 ·zLi α M β N (where 0 < z ≤ 50, and α and β are numerical values that give a stoichiometric ratio according to the type of element M). For example, when the element M contains Al, the sulfide solid electrolyte preferably has a composition represented by the general formula (100 - z)Li 10 GeP2S 12 ·zLi 3 / 2 Al 1 / 2 N (where 0 < z ≤ 50). When the sulfide solid electrolyte has such a composition, the ionic conductivity at 25 °C can be increased.

[0051] In the above general formula, z is more than 0 and 50 or less, preferably 1 or more and 45 or less, more preferably 3 or more and 35 or less, still more preferably 5 or more and 25 or less, and even more preferably 7 or more and 20 or less. When z in the above general formula is within the above range, the reduction resistance and the ionic conductivity at 25 °C can be further increased.

[0052] In the above general formula, α and β are numerical values ​​that give a stoichiometric ratio according to the type of element M. The values ​​of α and β are not particularly limited, but may be, for example, 0.80≦α≦3.0 and 0.10≦β≦1.2. In particular, when the element M contains Al, α=1.5 and β=0.5 may be used.

[0053] The ionic conductivity of the sulfide solid electrolyte at 25°C is 0.4×10 -3 S / cm or more is preferable, and 1.0×10 -3 More preferably, it is 1.5×10 S / cm or more. -3 When the ionic conductivity of the sulfide solid electrolyte at 25° C. is within the above range, the high-rate discharge performance of an all-solid-state battery including the sulfide solid electrolyte can be improved.

[0054] Thus, the sulfide solid electrolyte can be suitably used as a solid electrolyte for an all-solid-state battery.

[0055] <All-solid-state battery> The all-solid-state battery includes an anode layer, a solid electrolyte layer, and a cathode layer. FIG. 1 is a schematic cross-sectional view showing an all-solid-state battery according to one embodiment of the present invention. In an all-solid-state battery 10, which is a secondary battery, an anode layer 1 and a cathode layer 2 are disposed with a solid electrolyte layer 3 interposed therebetween. The anode layer 1 includes an anode substrate layer 4 and an anode mixture layer 5, and the anode substrate layer 4 is the outermost layer of the anode layer 1. The cathode layer 2 includes a cathode substrate layer 7 and a cathode mixture layer 6, and the cathode substrate layer 7 is the outermost layer of the cathode layer 2. In the all-solid-state battery 10 shown in FIG. 1, the cathode mixture layer 6, the solid electrolyte layer 3, the anode mixture layer 5, and the anode substrate layer 4 are laminated in this order on the cathode substrate layer 7.

[0056] In the all-solid-state battery, the anode layer 1, the solid electrolyte layer 3, the cathode layer 2, or a combination thereof contains the sulfide solid electrolyte. In the all-solid-state battery, the anode layer 1, the solid electrolyte layer 3, the cathode layer 2, or a combination thereof contains the sulfide solid electrolyte, and therefore the initial coulombic efficiency is excellent. Since the sulfide solid electrolyte has excellent resistance to reduction, it is preferable that the anode layer 1 and / or the solid electrolyte layer 3 contain the sulfide solid electrolyte. With the above configuration, the effect of the present invention is further improved.

[0057] The all-solid-state battery may use a solid electrolyte other than the sulfide solid electrolyte. The other solid electrolyte may be a sulfide solid electrolyte other than the sulfide solid electrolyte, or may be an oxide solid electrolyte, a dry polymer electrolyte, a gel polymer electrolyte, or a pseudo-solid electrolyte.

[0058] As the sulfide solid electrolyte other than the sulfide solid electrolyte, it is preferable that the Li ion conductivity is high, and for example, Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-Li3N, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S 2n (where m and n are positive numbers, and Z is Ge, Zn, or Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li δ XO ε (where δ and ε are positive numbers, and X is P, Si, Ge, B, Al, Ga, or In.) Li 10 GeP2S 12 Among these, Li2S-P2S5 is preferred, and xLi2S·(100-x)P2S5 (70≦x≦80) is more preferred, from the viewpoint of good lithium ion conductivity.

[0059] [Negative electrode layer] The negative electrode layer 1 includes a negative electrode substrate layer 4 and a negative electrode mixture layer 5 laminated on the surface of the negative electrode substrate layer 4. The negative electrode layer 1 may have an intermediate layer (not shown) between the negative electrode substrate layer 4 and the negative electrode mixture layer 5.

[0060] (Negative electrode base material layer) The negative electrode substrate layer 4 is a layer having electrical conductivity. The material of the negative electrode substrate layer 4 is not limited as long as it is an electrical conductor. For example, one or more metals selected from the group consisting of copper, aluminum, titanium, nickel, tantalum, niobium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, gold, silver, iron, platinum, chromium, tin, indium, alloys containing one or more of these metals, and stainless steel alloys can be used.

[0061] The lower limit of the average thickness of the negative electrode base layer 4 is preferably 3 μm, more preferably 5 μm, and even more preferably 8 μm. The upper limit of the average thickness of the negative electrode base layer 4 is preferably 200 μm, more preferably 100 μm, and even more preferably 50 μm. By setting the average thickness of the negative electrode base layer 4 to the above lower limit or more, the strength of the negative electrode base layer 4 can be sufficiently increased, and the negative electrode layer 1 can be formed well. By setting the average thickness of the negative electrode base layer 4 to the above upper limit or less, the volume of the other components can be sufficiently secured.

[0062] (Negative electrode mixture layer) The negative electrode mixture layer 5 can be formed from a so-called negative electrode mixture containing a negative electrode active material. The negative electrode mixture may contain a negative electrode mixture or a negative electrode composite containing a negative electrode active material and the sulfide solid electrolyte. The negative electrode mixture may contain optional components such as a solid electrolyte other than the sulfide solid electrolyte, a conductive agent, a binder, and a filler, as necessary.

[0063] <Negative electrode active material> As the negative electrode active material, a material capable of absorbing and releasing lithium ions is usually used. Specific examples of the negative electrode active material include Metals or metalloids such as Si and Sn; Metal oxides or semi-metal oxides such as Si oxide and Sn oxide; Polyphosphate compounds; Carbon materials such as graphite and non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon); Examples of the lithium metal composite oxide include lithium titanate.

[0064] The lower limit of the content of the negative electrode active material in the negative electrode mixture is preferably 10% by mass, more preferably 15% by mass. The upper limit of the content of the negative electrode active material is preferably 60% by mass, more preferably 70% by mass, even more preferably 80% by mass, particularly preferably 90% by mass, and may be 95% by mass. By setting the content of the negative electrode active material within the above range, the electric capacity of the all-solid-state battery can be increased.

[0065] <Negative Electrode Mixture or Negative Electrode Composite> The negative electrode mixture is a mixture prepared by mixing the negative electrode active material and the sulfide solid electrolyte by mechanical milling, etc. For example, the mixture of the negative electrode active material and the sulfide solid electrolyte can be obtained by mixing a particulate negative electrode active material and a particulate sulfide solid electrolyte. Examples of the negative electrode composite include a composite having a chemical or physical bond between the negative electrode active material and the sulfide solid electrolyte, a composite in which the negative electrode active material and the sulfide solid electrolyte are mechanically composited, etc. The composite is a composite in which the negative electrode active material and the sulfide solid electrolyte are present in one particle, and examples of the composite include a composite in which the negative electrode active material and the sulfide solid electrolyte form an aggregated state, a composite in which the sulfide solid electrolyte-containing coating is formed on at least a part of the surface of the negative electrode active material, etc. The negative electrode mixture or negative electrode composite may contain a solid electrolyte other than the sulfide solid electrolyte. The negative electrode active material contained in the negative electrode mixture and the sulfide solid electrolyte constitute a negative electrode mixture or a negative electrode composite, which can improve reduction resistance while maintaining high ionic conductivity, resulting in excellent initial coulombic efficiency.

[0066] When the negative electrode mixture contains a solid electrolyte, the lower limit of the content of the solid electrolyte in the negative electrode mixture may be 5 mass%, and preferably 10 mass%. The upper limit of the content of the solid electrolyte in the negative electrode mixture is preferably 90 mass%, more preferably 85 mass%, further preferably 80 mass%, and particularly preferably 75 mass%. By setting the content of the solid electrolyte in the above range, the electric capacity of the all-solid-state battery can be increased.

[0067] When the negative electrode layer contains the sulfide solid electrolyte, the lower limit of the content of the sulfide solid electrolyte in the negative electrode mixture may be 5 mass%, and preferably 10 mass%. The upper limit of the content of the sulfide solid electrolyte in the negative electrode mixture is preferably 90 mass%, more preferably 85 mass%, further preferably 80 mass%, and particularly preferably 75 mass%. By setting the content of the sulfide solid electrolyte in the negative electrode mixture within the above range, the initial coulombic efficiency of the all-solid-state battery can be further improved when the negative electrode layer contains the sulfide solid electrolyte.

[0068] <Other optional ingredients> The conductive agent is not particularly limited. Examples of such conductive agents include natural or artificial graphite, carbon black such as furnace black, acetylene black, and ketjen black, metals, and conductive ceramics. The conductive agent may be in the form of a powder or fiber. The content of the conductive agent in the negative electrode mixture may be, for example, 0.5% by mass or more and 30% by mass or less. The negative electrode mixture may not contain a conductive agent.

[0069] The binder (binding agent) is not particularly limited, and examples thereof include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyimide, and polyacrylic acid; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; and polysaccharide polymers.

[0070] The filler is not particularly limited, and examples of the main component of the filler include polyolefins such as polypropylene and polyethylene, silica, alumina, zeolite, glass, and carbon.

[0071] The lower limit of the average thickness of the negative electrode mixture layer 5 is preferably 30 μm, more preferably 60 μm. The upper limit of the average thickness of the negative electrode mixture layer 5 is preferably 1000 μm, more preferably 500 μm, and even more preferably 200 μm. By setting the average thickness of the negative electrode mixture layer 5 to the above lower limit or more, an all-solid-state battery having a high energy density can be obtained. By setting the average thickness of the negative electrode mixture layer 5 to the above upper limit or less, an all-solid-state battery having a negative electrode with excellent high-rate discharge performance and high active material utilization can be obtained.

[0072] (Middle class) The intermediate layer is a coating layer on the surface of the negative electrode base material layer 4, and contains conductive particles such as carbon particles to reduce the contact resistance between the negative electrode base material layer 4 and the negative electrode mixture layer 5. The configuration of the intermediate layer is not particularly limited, and can be formed, for example, from a composition containing a resin binder and conductive particles.

[0073] [Positive electrode layer] The positive electrode layer 2 includes a positive electrode substrate layer 7 and a positive electrode mixture layer 6 laminated on the surface of the positive electrode substrate layer 7. Like the negative electrode layer 1, the positive electrode layer 2 may have an intermediate layer between the positive electrode substrate layer 7 and the positive electrode mixture layer 6. This intermediate layer may have the same configuration as the intermediate layer of the negative electrode layer 1.

[0074] (Positive electrode substrate layer) The positive electrode substrate layer 7 may have the same configuration as the negative electrode substrate layer 4. The material of the positive electrode substrate layer 7 is not limited as long as it is a conductor. For example, it may be one or more metals selected from the group consisting of copper, aluminum, titanium, nickel, tantalum, niobium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, gold, silver, iron, platinum, chromium, tin, indium, and alloys containing one or more of these metals, and stainless steel alloys.

[0075] The lower limit of the average thickness of the positive electrode substrate layer 7 is preferably 3 μm, more preferably 5 μm. The upper limit of the average thickness of the positive electrode substrate layer 7 is preferably 200 μm, more preferably 100 μm, and even more preferably 50 μm. By making the average thickness of the positive electrode substrate layer 7 equal to or greater than the lower limit, the strength of the positive electrode substrate layer 7 can be sufficiently increased, and the positive electrode layer 2 can be formed satisfactorily. By making the average thickness of the positive electrode substrate layer 7 equal to or less than the upper limit, the volume of the other components can be sufficiently secured.

[0076] (Positive electrode mixture layer) The positive electrode mixture layer 6 can be formed from a so-called positive electrode mixture containing a positive electrode active material. The positive electrode mixture may contain a positive electrode mixture or a positive electrode composite containing a positive electrode active material and a solid electrolyte. As the solid electrolyte, the sulfide solid electrolyte may be used, but it is more preferable to use a solid electrolyte having high oxidation resistance. The positive electrode mixture forming the positive electrode mixture layer 6, like the negative electrode mixture, contains optional components such as a solid electrolyte, a conductive agent, a binder, and a filler as necessary. The positive electrode mixture layer may be in a form that does not contain a solid electrolyte.

[0077] <Cathode active material> The positive electrode active material contained in the positive electrode mixture layer 6 can be a known material that is generally used in all-solid-state batteries. x MeO y (Me represents at least one transition metal) x CoO2, Li x NiO2, Li x MnO3, Li x Ni α Co (1-α) O2, Li x Ni α Mn β Co (1-α-β) Li with spinel crystal structure such as O2 x Mn2O4, Li x Ni α Mn (2-α) O4, etc.), Li w Me x (A.O. y ) z(Me represents at least one transition metal, and A represents, for example, P, Si, B, V, etc.) polyanion compounds (LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc.) in the above formula. The elements or polyanions in these compounds may be partially substituted with other elements or anion species. In the positive electrode active material layer, one of these compounds may be used alone, or two or more of them may be used in combination.

[0078] Positive electrode active materials include lithium alloys such as Li-Al, Li-In, Li-Sn, Li-Pb, Li-Bi, Li-Ga, Li-Sr, Li-Si, Li-Zn, Li-Cd, Li-Ca, and Li-Ba, as well as compounds other than those represented by the above general formula, such as MnO2, FeO2, TiO2, V2O5, and V6O. 13 For example, a material having an oxidation-reduction potential higher than that of the negative electrode material, such as TiS2, can be used.

[0079] The lower limit of the content of the positive electrode active material in the positive electrode mixture is preferably 10% by mass, more preferably 15% by mass. The upper limit of the content of the positive electrode active material is preferably 60% by mass, more preferably 70% by mass, even more preferably 80% by mass, particularly preferably 90% by mass, and may be 95% by mass. By setting the content of the positive electrode active material within the above range, the electric capacity of the all-solid-state battery can be increased.

[0080] <Positive Electrode Mixture or Positive Electrode Composite> The positive electrode mixture is a mixture prepared by mixing the positive electrode active material and the solid electrolyte by mechanical milling, etc., in the same manner as in the case of the negative electrode. For example, the mixture of the positive electrode active material and the solid electrolyte can be obtained by mixing a particulate positive electrode active material and a particulate solid electrolyte. As in the case of the negative electrode, the positive electrode composite may be a composite having a chemical or physical bond between the positive electrode active material and the solid electrolyte, etc., or a composite obtained by mechanically combining the positive electrode active material and the solid electrolyte, etc. The composite is one in which the positive electrode active material and the solid electrolyte, etc. are present within one particle, and examples of the composite include one in which the positive electrode active material and the solid electrolyte, etc. form an aggregated state, and one in which a coating containing the solid electrolyte, etc. is formed on at least a part of the surface of the positive electrode active material. The positive electrode active material and the solid electrolyte contained in the positive electrode mixture constitute a positive electrode mixture or a positive electrode composite, so that high ionic conductivity can be maintained. As the solid electrolyte, the sulfide solid electrolyte may be used, but it is more preferable to use a solid electrolyte having high oxidation resistance.

[0081] When the positive electrode mixture contains a solid electrolyte, the lower limit of the content of the solid electrolyte may be 5 mass%, and preferably 10 mass%. The upper limit of the content of the solid electrolyte in the positive electrode mixture is preferably 90 mass%, more preferably 85 mass%, further preferably 80 mass%, and particularly preferably 75 mass%. By setting the content of the solid electrolyte in the above range, the electric capacity of the all-solid-state battery can be increased.

[0082] The lower limit of the average thickness of the positive electrode mixture layer 6 is preferably 30 μm, more preferably 60 μm. The upper limit of the average thickness of the positive electrode mixture layer 6 is preferably 1000 μm, more preferably 500 μm, and even more preferably 200 μm. By making the average thickness of the positive electrode mixture layer 6 equal to or greater than the lower limit, an all-solid-state battery having a high energy density can be obtained. By making the average thickness of the positive electrode mixture layer 6 equal to or less than the upper limit, an all-solid-state battery having excellent high-rate discharge performance and a negative electrode with a high active material utilization rate can be obtained.

[0083] [Solid electrolyte layer] The solid electrolyte layer 3 contains an electrolyte for the solid electrolyte layer. In addition to the above-mentioned sulfide solid electrolyte, examples of the electrolyte for the solid electrolyte layer include oxide solid electrolytes, other sulfide solid electrolytes, dry polymer electrolytes, gel polymer electrolytes, and pseudo-solid electrolytes. Among these, the sulfide solid electrolyte is preferred from the viewpoints of good ion conductivity and easy interface formation, and the sulfide solid electrolyte is more preferred. By containing the sulfide solid electrolyte in the solid electrolyte layer 3, the solid electrolyte layer maintains high ion conductivity while improving reduction resistance, and therefore the initial coulombic efficiency of the all-solid-state battery can be improved.

[0084] The electrolyte for the solid electrolyte layer may have a crystalline structure or may be amorphous without a crystalline structure. The electrolyte for the solid electrolyte layer may contain oxides such as Li3PO4, halogens, halogen compounds, etc.

[0085] The lower limit of the average thickness of the solid electrolyte layer 3 is preferably 1 μm, and more preferably 3 μm. The upper limit of the average thickness of the solid electrolyte layer 3 is preferably 50 μm, and more preferably 20 μm. By setting the average thickness of the solid electrolyte layer 3 to the above lower limit or more, it is possible to reliably insulate the positive electrode and the negative electrode. By setting the average thickness of the solid electrolyte layer 3 to the above upper limit or less, it is possible to increase the energy density of the all-solid-state battery.

[0086] [Manufacturing method of all-solid-state batteries] The manufacturing method of the all-solid-state battery mainly includes, for example, a sulfide solid electrolyte preparation step of preparing the sulfide solid electrolyte, a negative electrode mixture preparation step, a solid electrolyte layer electrolyte preparation step, a positive electrode mixture preparation step, and a lamination step of laminating the negative electrode layer, the solid electrolyte layer, and the positive electrode layer.

[0087] (Sulfide solid electrolyte production process) In this step, the sulfide solid electrolyte is produced, for example, by the following procedure. (1) Nitride (Li 3 / 2 Al 1 / 2 Preparation of N) Li3N and AlN are mixed in a mortar and then pelletized. Then, heat treatment is performed to produce Li 3 / 2 Al 1 / 2 N is produced. 3 / 2 Al 1 / 2 "N" is written as "Li3AlN2". (2) Preparation of sulfide solid electrolyte The above Li in a given molar ratio 3 / 2 Al 1 / 2 N, Li2S, and P2S5 are mixed in a mortar or the like, and then a sulfide solid electrolyte precursor is prepared. The sulfide solid electrolyte precursor can be prepared, for example, by mechanical milling or melt quenching. When preparing a sulfide solid electrolyte, a sulfide solid electrolyte precursor is prepared and then heat-treated at a temperature equal to or higher than the crystallization temperature, whereby the sulfide solid electrolyte can be prepared.

[0088] The crystallization temperature can be determined by measurement using a differential scanning calorimeter (DSC). For example, Li7P3S 11 In order to obtain a crystal structure, the heat treatment temperature is preferably 250°C or more and 400°C or less, and in order to obtain a β-Li3PS4 crystal structure, the heat treatment temperature is preferably 200°C or more and 400°C or less. This is because when heat treatment is performed at a high temperature such as 500°C, there is a possibility of phase transition to Li4P2S6, which is a stable phase. For example, in order to obtain a first crystal structure having diffraction peaks at 2θ=17.9°±0.5°, 19.1°±0.5°, 29.1°±0.5°, and 29.8°±0.5° in X-ray diffraction measurement using CuKα rays, the heat treatment temperature is preferably 250°C or more and 400°C or less.

[0089] In the above-mentioned preparation process, a sulfide solid electrolyte containing Al as the element M is prepared. However, by using a similar method to the above-mentioned preparation process, a sulfide solid electrolyte having a crystal structure containing N and at least one element M selected from the group consisting of Si, B, Mg, Zr, Ti, Hf, Ca, Sr, Sc, Ce, Ta, Nb, W, Mo, and V can be prepared. For example, Li 3 / 2 Al1 / 2 Li instead of N 3 / 2 B 1 / 2 N and Li 5 / 3 S 1 / 3 N, Li 9 / 5 S 3 / 10 By using N, etc., it is possible to prepare a sulfide solid electrolyte containing elements such as B and Si and N. In addition to the above-mentioned nitrides, LiMgN, LiCaN, LiHf 1 / 2 N, Li 3 / 2 Sc 1 / 2 N, LiZr 1 / 2 N, Li 5 / 3 Ti 1 / 3 N, Li 4 / 3 Ta 1 / 3 N, Li 7 / 4 Ta 1 / 4 N, Li 7 / 4 Nb 1 / 4 N, Li 3 / 2 W 1 / 4 N, Li 7 / 4 V 1 / 4 Examples include N.

[0090] In addition, in the above-described preparation process, a nitride composed of the elements M, Li, and N is used as the starting material, but the method for producing the sulfide solid electrolyte of the present embodiment is not limited to this.

[0091] In the above preparation process, a Li2S-P2S5-based sulfide solid electrolyte has been described as an example, but a sulfide solid electrolyte of LGPS type or argyrodite type can also be prepared by a similar preparation process. For example, in the above preparation process, the starting material is Li 3 / 2 Al 1 / 2 Although N, Li2S and P2S5 were used, a Ge-containing compound such as GeS2 may be further added to prepare a LGPS-type sulfide solid electrolyte containing Ge. More specifically, starting materials in a predetermined molar ratio are mixed in a mortar or the like, and then mechanical milling, such as ball milling or vibration milling, is performed to produce a sulfide solid electrolyte precursor, which is then heat-treated at a predetermined temperature or higher to produce the sulfide solid electrolyte. For example, Li 10 GeP2S 12 When preparing a sulfide solid electrolyte having a crystalline structure, the heat treatment temperature is preferably 300° C. to 1000° C., more preferably 350° C. to 700° C., further preferably 400° C. to 650° C., and particularly preferably 450° C. to 600° C. The heat treatment may be performed under a reduced pressure atmosphere or an inert gas atmosphere.

[0092] (Negative electrode mixture production process) In this step, a negative electrode mixture for forming a negative electrode layer is prepared. When the negative electrode mixture contains a mixture or composite containing a negative electrode active material and the sulfide solid electrolyte, this step includes mixing the negative electrode active material and the sulfide solid electrolyte by, for example, a mechanical milling method or the like to prepare a mixture or composite of the negative electrode active material and the sulfide solid electrolyte.

[0093] (Electrolyte manufacturing process for solid electrolyte layer) In this step, the above-mentioned electrolyte for the solid electrolyte layer is prepared to form the solid electrolyte layer. In this step, the electrolyte for the solid electrolyte layer can be obtained by processing a predetermined material for the electrolyte for the solid electrolyte layer by a mechanical milling method. The electrolyte for the solid electrolyte layer may be prepared by heating a predetermined material for the electrolyte for the solid electrolyte layer to a melting temperature or higher by a melting quenching method, melting and mixing the two at a predetermined ratio, and quenching. Other methods for synthesizing the electrolyte for the solid electrolyte layer include, for example, a solid-phase method in which the electrolyte is sealed under reduced pressure and fired, a liquid-phase method such as dissolution deposition, a gas-phase method (PLD), and firing in an argon atmosphere after mechanical milling. In addition, when the electrolyte for the solid electrolyte layer is the sulfide solid electrolyte, the above-mentioned sulfide solid electrolyte preparation step is performed in the preparation step of the electrolyte for the solid electrolyte layer.

[0094] (Positive electrode mixture production process) In this step, a positive electrode mixture for forming a positive electrode layer is prepared. The method for preparing the positive electrode mixture is not particularly limited and can be appropriately selected according to the purpose. For example, compression molding of the positive electrode active material, mechanical milling of a predetermined material of the positive electrode mixture, sputtering using a target material of the positive electrode active material, etc. can be mentioned. When the positive electrode mixture contains a mixture or composite containing the positive electrode active material and the sulfide solid electrolyte, this step includes, for example, mixing the positive electrode active material and the sulfide solid electrolyte using a mechanical milling method or the like to prepare a mixture or composite of the positive electrode active material and the sulfide solid electrolyte.

[0095] (Lamination process) In this process, an anode layer having an anode substrate layer and an anode mixture layer, a solid electrolyte layer, and a cathode layer having a cathode substrate layer and a cathode mixture layer are laminated. In this process, the anode layer, the solid electrolyte layer, and the cathode layer may be formed in sequence or in reverse, and the order of forming each layer is not particularly important. The anode layer is formed by pressure molding the anode substrate and the anode mixture, the solid electrolyte layer is formed by pressure molding an electrolyte for the solid electrolyte layer, and the cathode layer is formed by pressure molding the cathode substrate and the cathode mixture.

[0096] The negative electrode layer, the solid electrolyte layer, and the positive electrode layer may be laminated by pressure molding the negative electrode substrate, the negative electrode mixture, the electrolyte for the solid electrolyte layer, the positive electrode substrate, and the positive electrode mixture at the same time. The positive electrode layer, the negative electrode layer, or these layers may be molded in advance, and then pressure molded together with the solid electrolyte layer to laminate them.

[0097] [Other embodiments] The present invention is not limited to the above-described embodiment, and can be embodied in various other forms in addition to the above-described forms with various modifications and improvements.

[0098] The configuration of the all-solid-state battery according to the present invention is not particularly limited, and may include layers other than the negative electrode layer, the positive electrode layer, and the solid electrolyte layer, such as an intermediate layer or an adhesive layer.

[0099] <Example> The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0100] [Example 1] The following process produces 99(0.70Li2S 0.30P2S5) 1Li 3 / 2 Al 1 / 2 N was synthesized. Li3N and AlN were weighed out to a molar ratio of 1.2:1, mixed in a mortar, and pelletized. Then, the mixture was heat-treated at 750°C for 1 hour to obtain Li 3 / 2 Al 1 / 2 N was prepared. The Li 3 / 2 Al 1 / 2 N was determined by XRD measurement to be mainly composed of Li. 3 / 2 Al 1 / 2 It was confirmed that N. Next, Li2S (99.98%, Aldrich), P2S5 (99%, Aldrich), and Li3 / 2Al were dissolved in water in an argon atmosphere at a dew point of -50 °C or less in a glove box. 1 / 2 N was weighed out so that the molar ratio was 69.3:29.7:1.0, and then mixed in a mortar. This mixed sample was placed in a sealed 80 mL zirconia pot containing 160 g of zirconia balls with a diameter of 4 mm. A milling process was performed for 45 hours at a revolution speed of 510 rpm using a planetary ball mill (FRITSCH, model number Premium line P-7). Heat treatment was performed for 2 hours to obtain the sulfide solid electrolyte of Example 1. This heat treatment was performed at a temperature that was equal to or higher than the crystallization temperature, but not higher than 100°C above the crystallization temperature. The crystallization temperature was determined by measuring DSC. The DSC measurement was performed under the following conditions. That is, a DSC device (Rigaku, Thermo Plus DSC8230) was used, and a SUS sealed pan was used, and the temperature was raised from room temperature to 400°C at a rate of 10°C / min.

[0101] [Examples 2 to 9] The composition of sulfide solid electrolyte is (100-z)(0.70Li2S 0.30P2S5) zLi 3 / 2 Al 1 / 2The sulfide solid electrolytes of Examples 2 to 9 were synthesized in the same manner as in Example 1, except that the value of z in N was changed to 5, 7, 10, 15, 20, 25, 30, or 40.

[0102] [Example 10] Li2S, P2S5 and Li are used as raw materials for sulfide solid electrolytes. 3 / 2 Al 1 / 2 N, Li2S:P2S5:Li 3 / 2 Al 1 / 2 The sulfide solid electrolyte of Example 10 was synthesized in the same manner as in Example 1, except that the components were weighed out so that N=67.5:22.5:10.0 (mol %).

[0103] [Example 11] Li2S, P2S5 and Li are used as raw materials for sulfide solid electrolytes. 3 / 2 Al 1 / 2 N, Li2S:P2S5:Li 3 / 2 Al 1 / 2 A sulfide solid electrolyte of Example 11 was synthesized in the same manner as in Example 1, except that the components were weighed out so that N=35.0:35.0:30.0 (mol %).

[0104] [Example 12] Li2S, P2S5 and Li are used as raw materials for sulfide solid electrolytes. 3 / 2 Al 1 / 2 N, Li2S:P2S5:Li 3 / 2 Al 1 / 2 A sulfide solid electrolyte of Example 12 was synthesized in the same manner as in Example 1, except that the components were weighed out so that N=53.6:26.4:20.0 (mol %).

[0105] [Example 13] Li2S, P2S5 and Li are used as raw materials for sulfide solid electrolytes. 3 / 2 Al 1 / 2 N, Li2S:P2S5:Li 3 / 2 Al 1 / 2 A sulfide solid electrolyte of Example 13 was synthesized in the same manner as in Example 1, except that the components were weighed out so that N was 50.3:24.7:25.0 (mol %).

[0106] [Example 14] Li2S, P2S5 and Li are used as raw materials for sulfide solid electrolytes. 3 / 2 Al 1 / 2 N, Li2S:P2S5:Li 3 / 2 Al 1 / 2 A sulfide solid electrolyte of Example 14 was synthesized in the same manner as in Example 1, except that the components were weighed out so that N was 46.9:23.1:30 (mol %).

[0107] [Examples 15 to 18] Li3N and BN were weighed out so that the molar ratio was 1.1:1, mixed in a mortar, pelletized, and then heat-treated at 800°C for 10 minutes to obtain Li 3 / 2 B 1 / 2 N was prepared. The Li 3 / 2 B 1 / 2 N was determined by XRD measurement to be mainly composed of Li. 3 / 2 B 1 / 2 It was confirmed that N. Next, Li 3 / 2 Al 1 / 2 Li instead of N 3 / 2 B 1 / 2 N was used, and the sulfide solid electrolyte had the composition formula (100-z)(0.70Li2S 0.30P2S5) zLi 3 / 2 B 1 / 2 The sulfide solid electrolytes of Examples 15 to 18 were synthesized in the same manner as in Example 1, except that the value of z in N was changed to 1, 10, 20, or 30. [Examples 19 to 23] Li3N and Si3N4 were weighed out in a molar ratio of 5.1:1, mixed in a mortar, pelletized, and heat-treated at 800°C for 10 minutes to obtain Li 5 / 3 S 1 / 3 N was prepared. The Li 5 / 3 S 1 / 3 N was determined by XRD measurement to be mainly composed of Li. 5 / 3 S 1 / 3 It was confirmed that N. Next, Li 3 / 2 Al 1 / 2 Li instead of N 5 / 3 S 1 / 3N was used, and the sulfide solid electrolyte had the composition formula (100-z)(0.70Li2S 0.30P2S5) zLi 5 / 3 S 1 / 3 The sulfide solid electrolytes of Examples 19 to 23 were synthesized in the same manner as in Example 1, except that the value of z in N was changed to 1.5, 15, 20, 30, or 45.

[0108] [Comparative Example 1] The raw material for sulfide solid electrolyte is Li 3 / 2 Al 1 / 2 A sulfide solid electrolyte of Comparative Example 1 was synthesized in the same manner as in Example 1, except that N was not used.

[0109] [Reference example 1] 75Li2S·25P2S5 (Li3PS4) was synthesized by mechanical milling. In an argon atmosphere glove box with a dew point of -50°C or less, the raw materials of the sulfide solid electrolyte, Li2S and P2S5, were weighed so that Li2S:P2S5 = 75:25 (mol%), and then mixed in an agate mortar. The mixture was placed in a closed 80 mL zirconia pot containing 160 g of zirconia balls with a diameter of 4 mm. Milling treatment was performed for 45 hours at a revolution speed of 510 rpm using a planetary ball mill (FRITSCH, model number Premium line P-7). The sulfide solid electrolyte of Reference Example 1 was obtained by the above treatment.

[0110] [Reference example 2] Li 3 / 2 Al 1 / 2 A sulfide solid electrolyte of Reference Example 2 was synthesized in the same manner as in Example 1, except that Li3N was used instead of N and the value of z in the composition formula of the sulfide solid electrolyte (100-z)(0.70Li2S 0.30P2S5) zLi3N was changed to 20.

[0111] [Example 24] The following process results in 87.6(Li10GeP2S12)·12.4Li 3 / 2 Al 1 / 2 N was synthesized. Li3N and AlN were weighed out to a molar ratio of 1.2:1, mixed in a mortar, and pelletized. Then, the mixture was heat-treated at 750°C for 1 hour to obtain Li 3 / 2 Al 1 / 2 N was produced. Next, in an argon atmosphere glove box with a dew point of -50 °C or less, Li2S (99.98%, Aldrich), P2S5 (99%, Aldrich), GeS2 (99.99%, High Purity Chemical Laboratory), and Li 3 / 2 Al 1 / 2 N was weighed out to a molar ratio of 5:1:1:0.14, and then mixed in a mortar. This mixed sample was placed in a sealed 80 mL zirconia pot containing 160 g of zirconia balls with a diameter of 4 mm. Milling was performed for 40 hours at a revolution speed of 370 rpm using a planetary ball mill (FRITSCH, model number Premium line P-7). Thereafter, heat treatment was performed at 550°C for 8 hours to obtain the sulfide solid electrolyte of Example 24.

[0112] [Example 25, Example 26, Comparative Example 2] The composition of sulfide solid electrolyte is (100-z)(Li 10 GeP2S 12 )·zLi 3 / 2 Al 1 / 2 The sulfide solid electrolytes of Example 25, Example 26, and Comparative Example 2 were synthesized in the same manner as in Example 1, except that the value of z in N was changed to 30.2, 42.5, and 60.9. [Comparative Example 3] The raw material for sulfide solid electrolyte is Li 3 / 2 Al 1 / 2 A sulfide solid electrolyte of Comparative Example 3 was synthesized in the same manner as in Example 24, except that N was not used. [Reference example 3] The raw material for sulfide solid electrolyte is Li 3 / 2 Al 1 / 2 The sulfide solid electrolyte of Reference Example 3 was synthesized in the same manner as in Example 24, except that Li2O (99%, Kojundo Chemical Laboratory) was used instead of N and weighed out so that Li2S:P2S5:GeS2:Li2O = 4.86:1:1:0.14 (mol%). [Reference example 4] The raw material for sulfide solid electrolyte is Li 3 / 2 Al 1 / 2 The sulfide solid electrolyte of Reference Example 4 was synthesized in the same manner as in Example 24, except that Al2S3 (98%, Aldrich) was used instead of N and weighed out to give a ratio of Li2S:P2S5:GeS2:Al2S3 = 5:1:0.93:0.035 (mol%).

[0113] [evaluation] (1)XRD analysis X-ray diffraction measurements were performed by the following method. Using an airtight sample holder for X-ray diffraction measurements, the sulfide solid electrolyte powders of the examples and comparative examples were filled in an argon atmosphere with a dew point of -50°C or less. Powder X-ray diffraction measurements were performed using an X-ray diffractometer (Rigaku's "miniFlex II"). The radiation source was CuKα radiation, the tube voltage was 30 kV, the tube current was 15 mA, and the diffracted X-rays were passed through a 30 μm thick Kβ filter and detected by a high-speed one-dimensional detector (model number: D / teX Ultra2). The sampling width was 0.01°, the scan speed was 5° / min, the divergence slit width was 0.625°, the receiving slit width was 13 mm (OPEN), and the scattering slit width was 8 mm.

[0114] 2 shows X-ray diffraction (XRD) spectra in the range of 2θ=10° to 40° for Examples 1 to 3, 6, 8, 9, 10, and 11 and Comparative Example 1. Table 1 shows the crystal structures identified from the XRD spectra for Examples 1 to 23, Comparative Example 1, and Reference Example 2.

[0115] 8 shows X-ray diffraction (XRD) spectra in the range of 2θ=10° to 60° for Example 24, Comparative Example 3, and Reference Examples 3 and 4. Table 2 shows the crystal structures identified from the XRD spectra for Examples 24 to 26, Comparative Examples 2 and 3, and Reference Examples 3 and 4. Note that "Unknown" in Table 2 indicates that a diffraction peak was identified that could not identify a crystal structure.

[0116] (2) Raman spectroscopy The Raman spectrum was measured by the following method. A laser Raman spectrophotometer (Horiba, Ltd., "LabRAM HR Revolution") was used, and the excitation laser wavelength was 532 nm (YAG laser), the grating was 600 gr / mm, and the 100 cm -1 From 1800cm -1 Raman spectroscopy was performed in the wavenumber range of

[0117] 3 shows the Raman spectra of Examples 2 to 6 and Comparative Example 1. Table 1 shows the molecular structures identified from the Raman spectra of Examples 1 to 23, Comparative Example 1 and Reference Example 2.

[0118] (3) Ionic conductivity (σ) The ionic conductivity (σ) was determined at 25° C. by measuring AC impedance using Bio-Logic's VMP-300 according to the above-mentioned method.

[0119] In addition, for Examples 24 to 26, Comparative Examples 2 and 3, and Reference Examples 3 and 4, the ionic conductivity was also measured at temperatures of -30°C, -20°C, -10°C, 0°C, and 50°C, and the activation energy was calculated by the Arrhenius equation.

[0120] FIG. 4 shows the ionic conductivities at 25° C. of Examples 1 to 9 and Comparative Example 1, and Table 1 shows the ionic conductivities at 25° C. of Examples 1 to 23, Comparative Example 1 and Reference Example 2.

[0121] Table 2 shows the ionic conductivities and activation energies at 25° C. for Examples 24 to 26, Comparative Examples 2 and 3, and Reference Examples 3 and 4.

[0122] (4) Initial coulombic efficiency and charge / discharge performance (4-1) Preparation of positive electrode active material A LiNbO3 precursor solution was prepared by dissolving metallic Li in ultra-dehydrated ethanol, followed by dissolving niobium ethoxide (Nb(OC2H5)5). 0.8 Co 0.15 Al 0.05The surface of O2(NCA) particles was coated with LiNbO3 precursor. The LiNbO3-coated NCA was prepared by heat-treating the LiNbO3-coated NCA at 350℃ for 1 hour. This LiNbO3-coated NCA was used as the positive electrode active material.

[0123] (4-2) Fabrication of all-solid-state battery cell (Li-NCA half cell) LiNbO3-coated NCA and sulfide solid electrolyte (Li3PS4) of Reference Example 1 were weighed to LiNbO3-coated NCA:Li3PS4 = 70:30 (mass%), and then mixed in an agate mortar. The sulfide solid electrolyte of Example 1 was put into a powder molding machine with an inner diameter of 10 mm, and then pressure molded using a hydraulic press. After releasing the pressure, NCA-Li3PS4 mixed powder was put into one side of the solid electrolyte layer of Example 1 and pressure molded at 360 MPa per sample area for 5 minutes. After releasing the pressure, a metal Li foil was attached to the opposite side of the sulfide solid electrolyte layer of Example 1 and pressure molded to obtain a laminate of a positive electrode mixture layer, the sulfide solid electrolyte layer of Example 1, and a metal Li foil. This laminate was vacuum-sealed in an aluminum laminate cell and pressed using a stainless steel plate to obtain an all-solid-state battery cell (Li-NCA half cell).

[0124] All-solid-state battery cells (Li-NCA half cells) including the sulfide solid electrolytes of Examples 2, 4, and Comparative Example 1 were obtained by performing the same operation as in Example 1, except that the sulfide solid electrolyte of Example 1 was replaced with the sulfide solid electrolytes of Examples 2, 4, and Comparative Example 1.

[0125] (4-3) Charge / discharge test A charge / discharge test was performed on the above all-solid-state battery cell (Li-NCA half cell) under the following conditions. The charge / discharge test was performed in a thermostatic chamber at 50°C. Charging was performed at a constant current / constant voltage (CCCV) with a charging current of 0.125mA / cm2 and an upper charging voltage limit of 4.35V. The charging termination condition was until the charging current reached 0.0625mA / cm2. Discharging was performed at a constant current (CC) with a discharging current of 0.125mA / cm2 and a discharge termination voltage of 2.85V. The rest time between charging and discharging was 30 minutes. The percentage of the above initial discharge capacity relative to the initial charging amount of electricity at this time was calculated as the "initial coulombic efficiency (%)".

[0126] 5 shows the initial charge / discharge performance of Example 1, Example 2, Example 4, and Comparative Example 1. Table 1 shows the initial coulombic efficiency (%) of Example 1, Example 2, Example 4, and Comparative Example 1.

[0127] (5) Reduction resistance of sulfide solid electrolyte (5-1) Evaluation test using reduction resistance evaluation cell In a glove box in an argon atmosphere with a dew point of -50°C or less, the sulfide solid electrolyte of Example 1 and SUS316L powder were weighed to a mass ratio of 1:4, and then mixed in an agate mortar. The sulfide solid electrolyte (Li3PS4) of Reference Example 1 was put into a powder molding machine with an inner diameter of 10 mm, and then pressure molded using a hydraulic press. After releasing the pressure, the mixed powder of the SUS316 powder and the sulfide solid electrolyte powder of Example 1 was put into one side of the Li3PS4 layer and pressure molded at 360 MPa for 5 minutes. After releasing the pressure, a metal Li foil was attached to the opposite side of the Li3PS4 layer and pressure molded to obtain a laminate of the mixture layer of the sulfide solid electrolyte of Example 1, the Li3PS4 layer, and the metal Li foil. This laminate was sealed under reduced pressure in an aluminum laminate cell and compressed using a stainless steel plate to obtain a cell for evaluating reduction resistance, in which the mixture layer of the sulfide solid electrolyte of Example 1 was used as a working electrode and metal Li foil was used as a counter electrode. The charging test conditions were: measurement temperature 50°C, charging with constant current constant voltage (CCCV), and charging current 0.1mA / cm 2The lower limit potential of charging was 0.01 V, and the total charging time was 100 hours. Here, the reaction in which the mixture layer of the sulfide solid electrolyte of Example 1 is reduced is referred to as "charging". The amount of charged electricity 20 hours after the start of charging was taken as the reductive decomposition capacity (mAh / g) of the sulfide solid electrolyte after 20 hours. Since the SUS316L powder is stable at a potential of 0 V vs. Li / Li+, the only redox species is the sulfide solid electrolyte. Therefore, the amount of electricity flowing through this evaluation cell means the amount of reductive decomposition of the sulfide solid electrolyte. Using the same procedure, the sulfide solid electrolytes of Examples 2, 4, 8 to 17, 19, 20, and 22 and Comparative Example 1 were evaluated for reduction resistance.

[0128] Table 1 shows the reductive decomposition capacity after 20 hours from the start of charging for the sulfide solid electrolytes of Examples 1, 2, 4, 8 to 17, 19, 20, and 22 and Comparative Example 1.

[0129] (5-2) Evaluation test using all-solid-state battery cell (Li-Gr half cell) The sulfide solid electrolytes of Examples 24 to 26, Comparative Examples 2 and 3, and Reference Examples 3 and 4 were evaluated for reduction resistance by the following procedure.

[0130] Graphite particles (Gr) and the sulfide solid electrolyte (Li 10.21 GeP2Al 0.07 S 12 N 0.14 ) to Gr:Li 10.21 GeP2Al 0.07 S 12 N 0.14 After weighing out the two materials so that the ratio was 60:40 (mass%), they were mixed in an agate mortar. Li3PS4 was placed in a powder molding machine with an inner diameter of 10 mm, and then pressure-molded using a hydraulic press. After releasing the pressure, Gr-Li was applied to one side of the Li3PS4 layer. 10.21 GeP2Al 0.07 S 12 N 0.14The mixed powder was charged and pressure molded. After releasing the pressure, a metal Li foil was attached to the opposite side of the Li3PS4 layer and pressure molded to obtain a laminate of the sulfide solid electrolyte mixture layer of Example 24, the Li3PS4 solid electrolyte layer, and the metal Li foil. This laminate was vacuum sealed in an aluminum laminate cell and pressed using a stainless steel plate to obtain an all-solid-state battery cell (Li-Gr half cell) with the sulfide solid electrolyte mixture layer of Example 24 as the working electrode and the metal Li foil as the counter electrode.

[0131] All-solid-state battery cells (Li-Gr half cells) including the sulfide solid electrolytes of Examples 25, 26, and Comparative Example 3 were obtained by performing the same operation as in Example 24, except that the sulfide solid electrolyte of Example 24 was replaced with the sulfide solid electrolytes of Examples 25, 26, and Comparative Example 3.

[0132] A discharge test (lithiation of Gr) was carried out on the above all-solid-state battery cell (Li-Gr half cell) under the following conditions. The discharge test was carried out in a thermostatic chamber at 50°C. The discharge current was 0.125mA / cm 2 The battery was discharged at a constant current (CC) at 1000 V. The discharge capacity Q at this time was differentiated with respect to the voltage V to obtain a differential value dQ / dV, and a graph (dQ / dV curve) was plotted showing the relationship between the voltage V and the differential value dQ / dV.

[0133] 9 shows the dQ / dV curves of Examples 24 to 26 and Comparative Example 3. Table 2 shows the dQ / dV=-100mAhg of Examples 24 to 26 and Comparative Example 3. -1 V -1 The value of the voltage V at 0.4 V is shown in FIG. 9. It can be seen that the amount of change in dQ / dV is large around 0.4 V. The lithiation potential of Gr is about 0.1 V vs Li / Li. + Therefore, it is presumed that the change in dQ / dV near 0.4 V is due to the reductive decomposition of the sulfide solid electrolyte. -1 V -1 The shift in the value of the voltage V at 100° C. in the less noble direction means that the reductive decomposition potential of the sulfide solid electrolyte has shifted in the less noble direction, that is, the reduction resistance has improved.

[0134] (6) Atmospheric stability assessment In order to evaluate the chemical stability of the sulfide solid electrolyte in the atmosphere, the amount of hydrogen sulfide generated was measured. In a glove box with an argon atmosphere having a dew point of -50°C or less, 100 mg of the sulfide solid electrolyte powder of each of the examples and comparative examples was uniaxially press-molded at 360 MPa per sample area for 5 minutes using a powder molding machine with an inner diameter of 10 mm to obtain pellets. The obtained pellets were then placed in a sealed desiccator (effective volume 2100 cm). 3 The hydrogen sulfide generated was measured using a hydrogen sulfide sensor (TPA-5200E). The measurement was stopped when the hydrogen sulfide sensor's upper detection limit of 50 ppm was reached or when the measurement time had elapsed for 40 minutes. Amount of hydrogen sulfide generated from 1g of solid electrolyte V(cm 3 / g) is the obtained concentration C (ppm), the actual volume L of the desiccator (cm 3 ) and the pellet mass m (g) were used to calculate the mass using the following formula: V(cm 3 / g) = C × L × 10 -6 / m

[0135] 6 and 7 show the relationship between the time of exposure to the atmosphere (min) and the amount of hydrogen sulfide generated (cm) for the sulfide solid electrolyte pellets of the above-mentioned Examples and Comparative Examples. 3 1 is a graph showing the relationship between the amount of carbon dioxide and the surface area (g). FIG. 6 shows the amounts of hydrogen sulfide generated up to 20 minutes of exposure to the atmosphere in Examples 4 and 6 and Comparative Example 1, and FIG. 7 shows the amounts of hydrogen sulfide generated up to 40 minutes of exposure to the atmosphere in Example 6 and Reference Example 1.

[0136] [Table 1]

[0137] As shown in Table 1, the sulfide solid electrolytes of the Examples, which contain any one of Al, B, or Si as element M and N and have a crystal structure, had a suppressed reductive decomposition capacity 20 hours after the start of charging and excellent initial coulombic efficiency compared to the sulfide solid electrolyte of Comparative Example 1. The sulfide solid electrolytes of Examples 1, 2, 4 to 8, 10, 12 to 17, and 19 to 22 also had good ionic conductivity at 25°C. On the other hand, the sulfide solid electrolyte of Comparative Example 1, which did not contain the elements M and N, had good ionic conductivity, but the reductive decomposition capacity 20 hours after the start of charging was large and the initial coulombic efficiency was poor.

[0138] From Table 1, when the molar ratio of the Li content to the P content is 2.77 or more and 3.38 or less, and the molar ratio of the N content to the P content is 0.28 or more and 0.65 or less, 10 -3 Scm -1 Since a sulfide solid electrolyte having a structure that is expected to exhibit the above ionic conductivity and good atmospheric stability was obtained, it was confirmed that the composition of the sulfide solid electrolyte having such values ​​is particularly preferable. In addition, when the sulfide solid electrolyte contains Al as the element M, Li2S did not precipitate even when the content ratios of Li and N were large, such as the molar ratio of Li to P being 3.40 and the molar ratio of N to P being 0.71. This suggests that it is particularly preferable to contain Al as the element M.

[0139] As shown in FIG. 2, the sulfide solid electrolytes of all the examples and comparative examples were confirmed to have a crystal structure, with peaks observed in the XRD spectrum. 11, Example 3 had a crystal structure of β-Li3PS4, and Example 11 had a crystal structure of Li4P2S6. The crystal structures of the sulfide solid electrolytes of Examples 4 to 9 were specific crystal structure A having diffraction peaks at 2θ = 17.9 °, 19.1 °, 29.1 °, 29.8 °, and 30.9 °. The crystal structure of the sulfide solid electrolyte of Example 10 was confirmed to be specific crystal structure B having diffraction peaks at 2θ = 17.9 °, 19.1 °, 29.1 °, and 29.8 °.

[0140] As shown in the Raman spectrum of FIG. 3, the sulfide solid electrolyte of the embodiment becomes more and more complex with the bridging sulfur P2S7 as z increases, i.e., as the nitrogen (N) content increases. 4- The Raman shift of 406 cm -1 The peak near the PS4 3- The Raman shift of 423 cm -1 Therefore, the molecular structures of Examples 1 and 15 in Table 1 based on the Raman spectrum are PS4 3- , P2S7 4- and P2S6 4- The molecular structures of Examples 7 to 9, 11 to 14, and 20 to 22 based on Raman spectroscopy are presumed to be composed of PS4 3- It is presumed to consist of

[0141] 6 and 7, it was confirmed that the amounts of hydrogen sulfide generated in Example 4 and Example 6 were smaller than the amount of hydrogen sulfide generated in Comparative Example 1. In particular, Example 6, where z=20, exhibited a superior effect of suppressing hydrogen sulfide generation compared to Comparative Example 1 and Reference Example 1. This suggests that the sulfide solid electrolyte not only has high reduction resistance but also has excellent atmospheric stability. The reason why the sulfide-based solid electrolyte has a high effect of suppressing the generation of hydrogen sulfide is presumed to be as follows. As shown in the Raman spectrum of FIG. 3, the sulfide solid electrolyte of the example has a tendency to have a high hydrogen sulfide generation suppression effect as the z value increases, i.e., as the N content increases, the sulfide solid electrolyte of the example has a tendency to have a high hydrogen sulfide generation suppression effect as the z value increases. 4- The Raman shift of 406 cm -1The peaks around the Li2S region are reduced. In addition, in the XRD (X-ray diffraction) spectrum shown in FIG. 2, the sulfide solid electrolyte of the embodiment does not show any peaks derived from Li2S. From these facts, it can be seen that the sulfide solid electrolyte has a high N content and is stable in the atmosphere, i.e., the so-called bridged sulfur P2S7 4- It is presumed that the effect of suppressing the generation of hydrogen sulfide can be improved because (S3P-S-PS3) is reduced and Li2S, which easily reacts with water, is substantially not contained. In addition, Example 6 (z=20) is a bridged sulfur P2S7 4- The reason why the amount of hydrogen sulfide generated is less than that of Reference Example 1, which does not have N, is believed to be because the introduction of N into the structure of the solid electrolyte forms a three-dimensional network, strengthening the bonds. It is generally known that the introduction of N into oxynitride glass, in which part of the O in oxide glass is replaced with N, improves water resistance.

[0142] Comparing Example 6, Example 17, Example 21, and Reference Example 2, in which the N content is fixed at z=20 and y=0.70, it is found that Li2S precipitates only in Reference Example 2, which does not contain element M. From this, it is considered that the inclusion of element M can suppress the precipitation of Li2S.

[0143] The reason why the sulfide solid electrolyte contains the element M and thus can suppress the precipitation of Li2S is thought to be as follows. When Li3N is used as the starting material for the sulfide solid electrolyte containing N, Li3N reacts dramatically with P2S5, releasing N2 and precipitating Li2S. This is thought to be because the energy of N defect formation in Li3N is small. In contrast, in the present invention, α M β Since the N defect formation energy of N is greater than that of Li3N, it is believed that the reaction proceeds slowly during the synthesis of the sulfide-based solid electrolyte, suppressing the release of N2 and the precipitation of Li2S. The “defect formation energy” referred to here is a value calculated using the total energy Eperfect of a crystal structure containing no defects, the total energy Evacancy of a crystal structure containing defects, and the chemical potential μ of a defective atom, and refers to a parameter defined by the following formula. E defect = ( E vacancy + μ ) - E perfect

[0144] [Table 2]

[0145] As is clear from Table 2, the sulfur-based sulfide solid electrolyte containing Li, P, S, Ge, Al and N and having a crystal structure had excellent ionic conductivity at 25°C. Also, dQ / dV=-100mAhg -1 V -1 A shift in the value of the voltage V in the negative direction means that the reductive decomposition potential of the sulfide solid electrolyte has shifted in the negative direction, i.e., the reduction resistance has improved. Therefore, the sulfide solid electrolyte of the example was also excellent in reduction resistance. In particular, it was found that the sulfide solid electrolyte of Example 24 exhibited superior ionic conductivity at 25° C. compared with the sulfide solid electrolytes of Reference Examples 3 and 4.

[0146] The above results show that the sulfide solid electrolyte according to the present invention has high reduction resistance and can improve the initial coulombic efficiency of an all-solid-state battery including the sulfide solid electrolyte. It was also shown that the sulfide solid electrolyte according to the present invention can improve the atmospheric stability. [Industrial Applicability]

[0147] The all-solid-state battery including the sulfide solid electrolyte according to the present invention has excellent initial coulombic efficiency and is therefore suitable for use, for example, as a lithium-ion all-solid-state battery for HEVs. [Explanation of symbols]

[0148] 1. Negative electrode layer 2 Positive electrode layer 3 Solid electrolyte layer 4 Negative electrode base material layer 5. Negative electrode mixture layer 6 Positive electrode mixture layer 7 Positive electrode substrate layer 10 All-solid-state battery

Claims

[Claim 1] A sulfide solid electrolyte containing Al and N and having a crystal structure.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP2000340257A

  • Sulfide solid electrolyte, lithium solid battery and method for manufacturing sulfide solid electrolyte

    JP2018041671A